Analisis Pengaruh Attraction, Accessibility, dan Amenity terhadap Loyalitas Pelanggan tentang Niat Berkunjung Kembali di Agrowisata dan Waterpark Telaga Kusuma Karanganyar - Wisba Munawir Yusuf; Ihwan Susila (Jurnal Manajemen Dirgantara, 2024)
The purpose of this study was to analyze the influence of attractiveness, accessibility, and amenities on customer loyalty related to the intention to revisit Telaga Kusuma Karanganyar agrotourism and waterpark. This research method is quantitative. The type of data used in this study is primary data. The population in this study was all Telaga Kusuma Karanganyar Agrotourism and Waterpark. The sampling technique in this study used non-probability sampling. The number of samples in this study was 200 respondents. The data collection technique in this study used a questionnaire. The data analysis technique was carried out with the help of structural tests (SEM) and hypothesis tests (PLS), with SmartPLS software. The results showed that attractiveness had a positive and significant influence on customer loyalty. Accessibility had a positive and significant influence on customer loyalty. Amenities had a positive and significant influence on customer loyalty.